2016
DOI: 10.1080/10489223.2016.1187613
|View full text |Cite
|
Sign up to set email alerts
|

Influential factors in incomplete acquisition and attrition of young heritage speakers’ vocabulary knowledge

Abstract: This study investigates whether young heritage speakers, either simultaneous or sequential bilinguals, have limited vocabulary knowledge in their family language compared to matched monolingual counterparts and, if so, what factors help to account for this difference. These factors include age, age at emigration, length of emigration, frequency of heritage language use and parents' attitude towards heritage language acquisition and maintenance. Thirty young Persian-English bilinguals (aged 6 -18) living in New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 51 publications
1
18
1
Order By: Relevance
“…The narratives were then analyzed for ‘lexical richness’, a shorthand term in this article for both lexical diversity and sophistication. The way lexical competence was gauged in the present study it therefore different from what was done in Gharibi & Boers (2017), where ‘controlled’, decontextualized vocabulary tests served as the instruments. While these may be suitable for measuring declarative knowledge, they may not be as suitable for tapping procedural knowledge, that is, the knowledge speakers rely on when they engage in real-time, message-focused communication.…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…The narratives were then analyzed for ‘lexical richness’, a shorthand term in this article for both lexical diversity and sophistication. The way lexical competence was gauged in the present study it therefore different from what was done in Gharibi & Boers (2017), where ‘controlled’, decontextualized vocabulary tests served as the instruments. While these may be suitable for measuring declarative knowledge, they may not be as suitable for tapping procedural knowledge, that is, the knowledge speakers rely on when they engage in real-time, message-focused communication.…”
Section: Methodsmentioning
confidence: 78%
“…The two groups of young participants (and their parents) were the same as in Gharibi & Boers (2017). One group included 30 Persian-English bilinguals (14 boys and 16 girls; age range 6–18; mean age: 10.3) who have been living in New Zealand for different lengths of time (mean: 6.9 years).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, Gharibi and Boers (2017) that Turkish-English bilinguals' overall performance was degraded in comparison to their monolingual peers in all proficiency measures (lexical access, morphosyntactic complexity, and formal accuracy). In an attempt to account for the variation within the bilingual group, Schmid and Karayayla (2019) looked at the interaction between the proficiency measures and language background data.…”
Section: Variation Correlation and Complex Statistical Modellingmentioning
confidence: 75%
“…However, recent studies that include more nuanced methodology have revealed more ambiguous observations on the impact of language attitudes held by parents. Most recently, Gharibi and Boers (2017a) investigated lexical fluency (using productive/receptive vocabulary tests) among 30 heritage Persian speakers (both simultaneous and sequential) living in New Zealand, comparing them with matched monolingual counterparts in Iran. The parents of each heritage participant in the study were interviewed about their language attitudes towards Persian.…”
mentioning
confidence: 99%